2021
DOI: 10.1038/s41416-021-01507-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of clinical progression through plasma ctDNA in metastatic melanoma patients: a comparison to radiological progression

Abstract: Background The validity of circulating tumour DNA (ctDNA) as an indicator of disease progression compared to medical imaging in patients with metastatic melanoma requires detailed evaluation. Methods Here, we carried out a retrospective ctDNA analysis of 108 plasma samples collected at the time of disease progression. We also analysed a validation cohort of 66 metastatic melanoma patients monitored prospectively after response to systemic therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Our findings are in line with other published studies regarding the usefulness of ctDNA to monitor treatment success. Differences in the results can be explained by different study designs and patient populations [ 2 , 6 , 7 , 8 , 9 , 20 ]. Most of these were small retrospective studies with a short observation period and inconsistent sampling time points [ 8 , 9 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in line with other published studies regarding the usefulness of ctDNA to monitor treatment success. Differences in the results can be explained by different study designs and patient populations [ 2 , 6 , 7 , 8 , 9 , 20 ]. Most of these were small retrospective studies with a short observation period and inconsistent sampling time points [ 8 , 9 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these routine blood markers lack sufficient specificity and sensitivity for the prediction of treatment response and prognosis. For the detection of tumor progression, imaging with PET-CT scans is still the recommended method [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our results indicated that a liquid biopsy from blood might yield a better representation of the overall spectrum of somatic variants present in the tumor, particularly in the case of metastatic patients. ccfDNA from blood likely contains tumor DNA from multiple tumor localizations, which can better assist in personalized therapy of primary and metastatic brain tumor patients [ 49 , 50 , 51 , 52 ]. A liquid biopsy from blood may be a plausible alternative for elderly brain tumor patients in which a biopsy of CSF is not recommended due to its invasiveness and danger of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies show that ctDNA levels correlate well with tumor load and therefore ctDNA dynamics can be used as a surrogate of treatment response (86)(87)(88). In addition, the modification of the ctDNA methylation profile has been proposed as an alternative biomarker for treatment response (89).…”
Section: Ctdna To Monitor Treatment Outcomesmentioning
confidence: 99%